2011
DOI: 10.3389/fpsyg.2011.00273
|View full text |Cite
|
Sign up to set email alerts
|

Bilingualism and Creativity: Benefits in Convergent Thinking Come with Losses in Divergent Thinking

Abstract: Bilingualism is commonly assumed to improve creativity but the mechanisms underlying creative acts, and the way these mechanisms are affected by bilingualism, are not very well understood. We hypothesize that learning to master multiple languages drives individuals toward a relatively focused cognitive-control state that exerts strong top-down impact on information processing and creates strong local competition for selection between cognitive codes. Considering the control requirements posed by creativity tas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
83
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(97 citation statements)
references
References 35 publications
4
83
0
2
Order By: Relevance
“…Competitive control requires a narrowing of attention that is arguably enhanced when participants must use one rather than another language in a dual language context. An ingenious experiment by Wu and Thierry (2013) found that during a dual language context, bilinguals were indeed more effective at resisting non-verbal interference as tested in a non-verbal flanker task (see also (Hommel et al 2011) for evidence of benefits on a convergent thinking task). Cooperative control, by contrast, is predicted to increase the breadth of attention.…”
Section: Language Control Statesmentioning
confidence: 99%
“…Competitive control requires a narrowing of attention that is arguably enhanced when participants must use one rather than another language in a dual language context. An ingenious experiment by Wu and Thierry (2013) found that during a dual language context, bilinguals were indeed more effective at resisting non-verbal interference as tested in a non-verbal flanker task (see also (Hommel et al 2011) for evidence of benefits on a convergent thinking task). Cooperative control, by contrast, is predicted to increase the breadth of attention.…”
Section: Language Control Statesmentioning
confidence: 99%
“…It is comprised of four scales: fluency (the number of ideas and solutions), originality (the rarity of ideas), elaboration (the number of added ideas, and the ability to develop and elaborate on ideas), and flexibility (the number of different categories of relevant responses being used) (Craft, 2001;Hommel, Colzato, Fischer, & Christoffels, 2011;Villalba, 2008). Since half of the participants did not have English knowledge the Persian translation of this test was used.…”
Section: Torrance Test Of Creative Thinking (Ttct)mentioning
confidence: 99%
“…Furthermore, he asserted that most studies were conducted on children and employed measures of divergent thinking to assess creativity. Hommel, Colzato, Fischer, and Christoffels (2011) affirmed the positive impact of bilingualism on creativity, positing that it is the underlying processes and mechanisms of creativity that are influenced by bilingual practice not the unitary concept per se.…”
Section: Introductionmentioning
confidence: 99%
“…The most common question type used in such systems tends to be based on convergent, selected responses. Some practitioners have argued that the practice has little pedagogic value beyond testing surface learning (Hommel et al 2011).In solving a two-step arithmetic word problem for instance, selecting a single best answer among other options for grading presents some difficulties. First, only the final answer is compared against the correct answer, making it difficult to obtain intermediate results or award partial marks as possible with paper based assessments.…”
Section: Introductionmentioning
confidence: 99%